From paternalistic stereotypes to overtly negative storytelling: A critical narrative analysis of how British Conservative leaders talk about young people (2005-2022) - Alma-Pierre Bonnet (Revue LISA)
The Conservative Party has never really been popular with young people. The early part of the 21st century was marked by several attempts to change this situation. For example, David Cameron tried to decontaminate the Conservative brand by making his party appear more inclusive and in line with topics that would resonate with younger voters, such as the environment and gay rights. Yet, in 2019, after almost a decade in power, the Conservatives scored very low among younger voters, when they nonetheless achieved one of their most important electoral victories in decades. This apparent lack of representativeness might account for the growing youth disillusionment in politics. In what amounts to a vicious circle, politicians and political parties tend to ignore the needs of those who do not vote for them. In this paper, we posit that this vicious circle is not an inevitable political fact and we argue that it is actually fuelled, in part, by the negative representation of young people in the speeches delivered by Tory leaders. To verify this hypothesis, we propose a critical analysis of the narratives used by various Conservative leaders to talk about young people during the party’s annual conferences, from 2005 to 2022.